Research on the capsules of libido-bavachin for improve the sports physical function and cognitive psychological abilities and mental energy to strength training in female swimmers - Chen, N.; Chen, X.; Li, J.; Liu, J. (2001)
Strength training (S.T.) is a training model of the Chinese swimming team. On the basis of the study on animal experiments using the mixture of Libido-Bavachin (which have been reported in the relevant articles), the aim of this study was to investigate influences on the female athlete swimmers physical functions and the changes of sports cognitive psychological abilities and mental energy after S.T. 15 girls were given the capsules for 30 days. Sports physical functions, cognitive psychological abilities and mental energy were tested. We found that the capsules could increase hemoglobin (p<0.05) and blood testosterone levels significantly (p<0.01), reduce heart rate (p<0.01) and blood lactate significantly (p<0.01) in strengthening training and decrease pulse (p<0.01), blood urea nitrogen (p<0.01) and creatine kinase (p<0.01) notably the next morning after strength training. In the meantime, the sports cognitive psychological abilities also increased significantly. Especially visual memory (VM) and operation thinking (OT), time & space judgement ability (TSJ) increased (p<0.01). Sympathetic reaction (SR), spatial direction judgement ability (SDJ), motion-sense time estimation ability (MST), had also been significantly enhanced (p<0.05) after S.T. Mental energy testing improved also. Achievement motive level of young swimmers raised more rapidly after S.T. (p<0.01). Self-encouragement level of participants also improved. Most players felt much more vigorous and gumptious. The results indicate that the capsules can increase sports physical functions and psychological cognitive abilities or mental energy, accelerate protein synthesize, reduce protein destruction, and speed up the recovery of cognitive psychological abilities or mental energy. It was said that the capsules of Libido-Bavachin mixture could activate sports physical function and psychological cognitive abilities or mental energy and maintain the situation.